Kerajaan Seribu Tahun Berdasarkan (Wahyu 20:1-6) - Hot Nome; Aprianus Lendrik Moimau (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The Millennium Age, which is the thousand-year period of Christ's reign on earth, is rarely discussed in writings about the End Times, but it's actually an intriguing topic to delve into. During this period, Satan will be bound and unable to do evil, with angels responsible for his confinement. This is aimed at preventing Satan from deceiving the nations. Although eventually he will be released for a short time. After the Great Tribulation period, which is a seven-year period of great difficulty for the world, the Millennium Age will come, considered as the golden age of the world. Here, humanity will live in peace and prosperity, with ages of hundreds of years considered normal. Children will lead wild animals that were previously considered dangerous to humans. And everyone will know the Lord during that time.